Evaluation of tert‐Butyl Isosteres: Case Studies of Physicochemical and Pharmacokinetic Properties, Efficacies, and Activities. Issue 3 (28th January 2015) - Westphal, Matthias V.; Wolfstädter, Bernd T.; Plancher, Jean‐Marc; Gatfield, John; Carreira, Erick M.
Abstract The tert‐butyl group is a common motif in medicinal chemistry. Its incorporation into bioactive compounds is often accompanied by unwanted property modulation, such as increased lipophilicity and decreased metabolic stability. Several alternative substituents are available for the drug discovery process. Herein, physicochemical data of two series of drug analogues of bosentan and vercirnon are documented as part of a comparative study of tert‐butyl, pentafluorosulfanyl, trifluoromethyl, bicyclo[1.1.1]pentanyl, and cyclopropyl‐trifluoromethyl substituents.